2021
DOI: 10.1094/phyto-12-20-0543-r
|View full text |Cite
|
Sign up to set email alerts
|

Aureoverticillactam, a Potent Antifungal Macrocyclic Lactam from Streptomyces aureoverticillatus HN6, Generates Calcium Dyshomeostasis-Induced Cell Apoptosis via the Phospholipase C Pathway in Fusarium oxysporum f. sp. cubense Race 4

Abstract: Extensive efforts have been devoted to discover new bio-fungicides of high efficiency for control of Fusarium oxysporum f. sp. cubense race 4 (Foc4), a catastrophic soil-borne phytopathogen causing banana fusarium wilt worldwide. In this paper, aureoverticillactam (YY3) was verified to possess a potent antifungal activity against Foc4 for the first time, with the EC50 values of 20.80 μg/ml against hyphal growth, and 12.62 μg/ml against spore germination. To provide insight into its action mechanism, the cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…displayed similar ROS-mediated mitochondrial apoptotic phenotypes in F. oxysporum induced by cinnamaldehyde or aureoverticil lactam. , Kai et al showed that chlorogenic acid inhibits Fusarium fujikuroi growth by triggering cellular ROS accumulation, thereby further inducing cell apoptosis in this pathogen . Liang et al reported that surfactin displays antifungal activity against F.…”
Section: Discussionmentioning
confidence: 99%
“…displayed similar ROS-mediated mitochondrial apoptotic phenotypes in F. oxysporum induced by cinnamaldehyde or aureoverticil lactam. , Kai et al showed that chlorogenic acid inhibits Fusarium fujikuroi growth by triggering cellular ROS accumulation, thereby further inducing cell apoptosis in this pathogen . Liang et al reported that surfactin displays antifungal activity against F.…”
Section: Discussionmentioning
confidence: 99%
“…Being Ca 2+ an essential signaling ion, proteins involved in its homeostasis are increasingly studied as potential targets of antifungal drugs ( Kwun et al, 2021 ; Li et al, 2021 ; Wang et al, 2021 ). A model of Ca 2+ signaling could be used to predict the outcomes of the inhibition of a particular protein on the calcium physiology of fungal cells, thus helping to identify the best drug targets.…”
Section: Discussionmentioning
confidence: 99%
“…In that order, 1 mL of supernatant was diluted to 10 -7 , 10 -8 , and 10 -9 . Aliquots of 25 μL were spread onto Koch’s One solid medium using a bent rod ( Wang et al., 2021b ). The culture was spread evenly and incubated for 5 d at 28°C.…”
Section: Methodsmentioning
confidence: 99%
“…Chlorophyll content, root vigor, soluble reducing sugar content, soluble protein content, catalase activity, and free amino acid content of cowpea seedlings were determined using the plant chlorophyll content test kit from Beijing Solabao Technology Co Ltd. Previously reported method were followed for TTC ( Zhang et al., 2015 ), anthrone colorimetric, UV absorption and potassium permanganate titration ( Wang et al., 2021b ), ninhydrin color development ( Lu and Mallette., 1970 ).…”
Section: Methodsmentioning
confidence: 99%